Nigeria management manpower development in the context of globalization: an evaluation (2006)
In this paper, management development is viewed for national development that enbales the Nigerian nation to meet up with the rest of the world in the context of globalization. The paper defines management, management manpower education and globalisation. It views information the beacon of globalization. It therefore, posits that the effective use of information and communication in globalization cannot be downplayed. The paper reports an assessment of a new management training instituitons do not normally conduct training needs assessment; they were strong in the areas of provision of libraries, course materials, number of trainers among others. The recommendations include:proper and adequate funding of the institutions and making them more relevant by equipping them and exposing them to universal practices.